Introducing Facetometrics:A New Keyword-Based Measure for Locating Research Areas of a Subject - Jana, Kalipada; Dutta, Bidyarthi (Journal of Information and Knowledge, 2016)
This paper has introduced a technique to find out research areas in a subject by the analysis of keywords assigned to articles. Keywords assigned to 1227 research papers published between 2004 and 2013 in a specific subject area "Hawking radiation" have been collected and analyzed. The research articles were retrieved from Web of Science using the search term "Hawking Radiation". The assigned keywords occurred with different frequencies. The keywords formed the clusters of words. The names given to the clusters were in accordance with the names of the most frequently occurring word in a keyword clusters. The clusters have been classed into three groups by size, i.e. small cluster, medium cluster and large cluster. As fairly large number of keywords formed large clusters, it has been assumed that the potential facets are represented by such clusters. Three basic parameters associated with the keyword clusters were identified, viz. no. of keywords in a cluster, frequency of occurrence and occupancy. Four indicators, viz., stability index, integrated visibility index, momentary visibility index and potency index have been defined on the basis of these three parameters and their fluctuations over the study period have been noticed. These indicators hold different values for different clusters and facets. The value ranges of these are categorized in five groups, viz. very high, high, medium, low and very low. Each indicator describes a particular aspect of a facet. These indicators may be used to measure various aspects of facets.